Add <math><mstyle displaystyle="true"><mn>2</mn><mi>b</mi></mstyle></math> and <math><mstyle displaystyle="true"><mn>5</mn><mi>b</mi></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>32</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mn>25</mn></mstyle></math> to both sides of the equation.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>25</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>25</mn></mstyle></math> .

Divide each term in <math><mstyle displaystyle="true"><mn>7</mn><mi>b</mi><mo>=</mo><mn>0</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Simplify the left side.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify the right side.

Divide <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Do you know how to Solve for b 2b-25+5b=7-32? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.